2009
DOI: 10.1007/s00259-009-1334-3
|View full text |Cite
|
Sign up to set email alerts
|

The added value of multislice SPECT/CT in patients with equivocal bony metastasis from carcinoma of the prostate

Abstract: The addition of SPECT/CT resulted in a significant reduction of equivocal reports; a definitive diagnosis was given in the majority of the patients due to the improved diagnostic confidence compared to planar or SPECT imaging alone in prostate cancer patients with suspected bone metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
100
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(118 citation statements)
references
References 13 publications
7
100
0
11
Order By: Relevance
“…Conventional planar bone scintigraphy (pBS) with 99m Tc-labeled radiopharmaceuticals, such as hydroxyethylene-diphosphonate ( 99m Tc-HDP), is still the most frequently used modality for diagnosing bone metastases (3). Studies have shown that adding SPECT/CT to pBS improves the specificity and positive predictive value (PPV) as well as the diagnostic confidence of the reader, thereby reducing the number of equivocal study reports (4,5). 18 F-sodium fluoride ( 18 F-NaF) was introduced in 1962 by Blau et al (6).…”
mentioning
confidence: 99%
“…Conventional planar bone scintigraphy (pBS) with 99m Tc-labeled radiopharmaceuticals, such as hydroxyethylene-diphosphonate ( 99m Tc-HDP), is still the most frequently used modality for diagnosing bone metastases (3). Studies have shown that adding SPECT/CT to pBS improves the specificity and positive predictive value (PPV) as well as the diagnostic confidence of the reader, thereby reducing the number of equivocal study reports (4,5). 18 F-sodium fluoride ( 18 F-NaF) was introduced in 1962 by Blau et al (6).…”
mentioning
confidence: 99%
“…Una de las mayores ventajas del gammagrama óseo es que requiere un mínimo del 5% de tasa de recambio óseo para poder detectar una lesión, mientras que los estudios anatómicos como la radiografía requieren un mínimo del 40-50% de dicho recambio para la visualización. Tiene una elevada sensibilidad para la detección de metástasis óseas (llega a ser hasta del 96.9%) 10 ; la mayor desventaja de dicho estudio es su baja especificidad, que puede variar del 41 al 57% 10,11 . Por tal motivo, los equipos híbridos (tomografía por emisión de fotón simple con tomografía computarizada [SPECT/CT]) permiten mejorar dicha especificidad, al fusionar los hallazgos con un estudio tomográfico, logrando una especificidad de hasta el 82%11 (Fig.…”
Section: Metilendifosfonatounclassified
“…This feature provides elevated sensitivity for the detection of bone metastases, which can be as high as 96.9% 10 . However, the greatest disadvantage of this study is its low specificity, which can range from 41 to 57% 10,11 . For this reason, hybrid equipment (SPECT/CT) allows for such specificity to be improved by merging the findings with a CT study, with up to 82% specificity being attained (Fig.…”
Section: Radiotracers Used For Scintigraphy Plus Spect/ct 99mtc-mdpmentioning
confidence: 99%